PENGARUH BUDAYA ORGANISASI, KOMITMEN KERJA DAN KEPUASAN KERJA TERHADAP MOTIVASI PEGAWAI DI KANTOR DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU ATAP KABUPATEN BANTAENG - Suhaeni Syamsuddin (FEB Universitas Lakidende, 2020)
This research aims to find out and analize the influence of organizational culture, work commitment and job satisfaction simultaneously on employee motivation, organizational cultural influence, work commitment and job satisfaction participating in the motivation of employees in the Office of The Office of Investment and Integrated One-Stop Service of Bantaeng Regency. The sample used the saturated method of 45 employee respondents. The method of data analysis used is multiple linear regression analysis. The results of the analysis showed that organizational culture, work commitment and job satisfaction were influenced together on employee motivation and organizational culture, work commitment and job satisfaction that influenced the motivation of employees in the Office of Investment and Integrated One-Stop Service of Bantaeng Regency